Konstruksi Keluarga Ideal dalam Perspektif Manajemen Dakwah - Yayah Daryati, Nierna; Rahman, M. Taufiq; Huriani, Yeni (Tadbir: Jurnal Manajemen Dakwah, 2025)
This article presents a critical academic review of Penny Edgell’s analysis of the construction of the “ideal family” in religious discourse, examined through the perspective of da‘wah management. Employing an analytical literature review, this study explores how religious institutions operate as da‘wah actors that systematically produce, manage, and reproduce normative family ideals through religious rhetoric, community practices, and family-oriented programs. The analysis demonstrates that family da‘wah functions not merely as the transmission of doctrinal teachings, but as a managerial process that shapes moral frameworks, symbolic boundaries, and evaluative standards of “good,” “normal,” and “problematic” families. By critically engaging Edgell’s framework, this article highlights its limitations when applied to the Indonesian Muslim context, which is characterized by plural religious authorities and diverse da‘wah practices. Accordingly, the article proposes a sociological da‘wah perspective as a conceptual enhancement for family da‘wah management, one that views da‘wah as a dialogical and contextual social praxis attentive to women’s agency and the lived realities of Muslim families. This study contributes to da‘wah management scholarship by advancing a sociological understanding of how da‘wah institutions shape family norms and social morality.